O sebastianismo em São João de Pirabas: sincretismo religioso e memória popular de um rei que de colonizador se torna afro brasileiro - FERREIRA, Giovana de Cássia Araújo (2024)
This research aims to understand the syncretic-religious triad that adorns Piraba's Sebastianism and which gave rise to “our Sabá King” and why the firm presence of beliefs and their importance for the construction of local identity. Oral history was the methodology used to prepare this article, as “Our Sabá King” is part of the community's experience, in the memory of the fishermen and in the very strong beliefs and cults of the population, especially the Umbanda faithful. Therefore, it is important to highlight how oral narratives support and perpetuate this myth in our municipality. From Sebastianism in Piraba, legends, tales, myths, history and cures emerge that populate the imagination of the region, which, paradoxically, (re)feed the One-Trinity that is inscribed in the Sebastian myth and operates as its support. Many questions were asked, all so that it could be understood, who would be King Sabá at the end of the Castle? What relationship would he have with D. Sebastião and S. Sebastião? How important is it to the community and why is it important? Why is there such a strong cult and devotion among the residents of this region? And how is the relationship with religious syncretism?